PENGELOLAAN RETRIBUSI PASAR SENTRAL KOTA KENDARI DALAM MENINGKATAN PENDAPATAN ASLI DAERAH - Muh. Amir; Liwaul Liwaul (Universitas Halu Oleo, 2020)
The research objective was to determine the Management of Central Market Retribution in Kendari City to Increase Local Revenue. The research method used is a qualitative technique, namely interactive analysis techniques, which have stepped through data reduction, data presentation and conclusion drawing. The subjects in this research were employees of the Kendari City Tax and Retribution Management Agency, by determining 5 research informants purposively. The results of this research indicate that the management of market fees is not optimal, this can be seen in the ineffective planning of market levy management, because it is not supported by accurate data regarding the potential of the central market, especially traders who have no place in the market. Organizing has also not been effective, in terms of working standards, the attitudes of the central market levies that have not complied with the rules in its implementation, such as rules on working hours, and discrimination in the collection. In the case of the collectors' remuneration that is not on time, and under supervision is still lacking and only relies on reports of monthly revenue. The acceptance of market retribution has also not reached the target, due to the inadequate implementation of the management function, particularly the supervisory function.